SUBSTANCE USE AND KNOWLEDGE AMONG ITALIAN HIGH SCHOOL STUDENTS - Spacilova, Lenka; Klusonova, Hana; Petrelli, Fabio; Signorelli, Carlo; Visnovsky, Peter; Grappasonni, Iolanda (Biomedical papers, 2009)
Aims: This study was aimed for evaluation of Italian students' attitudes to addictive substances, their knowledge and personal experience, and their awareness about the risks.Methods: The research was realized among high school students from Marche region in the Central Italy in the year 2006; the study group was randomly chosen from all schools in the region. 4118 appropriately completed questionnaires returned. The statistic processing was carried out by using chi-square test for two qualitative variables.
Keywords: Drug usage/High school students/Italy